EVALUATION OF COORDINATION IN IMPROVING QUALITY OF SERVICE DURING THE COVID-19 PANDEMIC - Novita Rosanti; Siti Fatimah; Verawaty Verawaty; Sujatmiko Sujatmiko (Yayasan Education and Social Center, 2022)
Coordination is an obligation that connects leaders and subordinates. Therefore, the attitude of employees is strongly influenced by the nature of their leadership. If a leader does not provide direction and lacks communication, the organization will not work according to the plan. When viewed from its function, coordination is closely related to communication. This study uses descriptive qualitative research methods. This research uses data collection techniques such as interviews, observations, and documentation to collect data. The study results illustrate how to coordinate during the covid-19 pandemic period, hold official meetings between one unit and another, name someone as an exceptional coordinator, have designed work guidelines, leaders always organize meetings with their members and prepare coordination facilities and infrastructure. Coordination obstacles he faced include: first, personal barriers, namely the implementation of online meetings, making participants less conducive and less communicative to express their opinions. Second, physical barriers are participants in online meetings or meetings sometimes encounter obstacles on the Internet. The sound is cut and will not be understood clearly, and the video quality is poor